Stress Biomarkers, Mood States, and Sleep during a Major Competition: “Success” and “Failure” Athlete's Profile of High-Level Swimmers - Chennaoui, Mounir; Bougard, Clément; Drogou, Catherine; Langrume, Christophe; Miller, Christian; Gomez-Merino, Danielle; Vergnoux, Frédéric (Frontiers in Physiology, 2016)
The aim of this study was to evaluate stress markers, mood states and sleep indicators in high-level swimmers during a major 7-days competition according to the outcomes. Nine swimmers (6 men and 3 women (age: 22 ± 2 years and 22 ± 4 years, respectively) were examined. Before (PRE) and after (POST) each race (series, semi-finals and finals), salivary concentrations of cortisol, α-amylase (sAA) and chromogranin-A (CgA) were determined. Mood states were assessed by the profile of mood state (POMS) questionnaire completed before and after the 7-days, and self-reported sleep diaries were completed daily. In the “failure” group, cortisol and sAA significantly increased between PRE-POST measurements (p<0.05), while sCgA was not changed. Significant overall decrease of cortisol (-52.6%) and increase of sAA (+68.7%) was shown in the “failure group”. In this group, fatigue, confusion and depression scores and sleep duration before the finals increased. The results in the “success” group show tendencies for increased cortisol and sCgA concentrations in response to competition, while sAA was not changed. Cortisol levels before the semi-finals and finals and sCgA levels before the finals were positively correlated to the fatigue score in the “failure” group only (r=0.89). sAA levels before and after the semi-finals were negatively correlated to sleep duration measured in the subsequent night (r=-0.90). In conclusion, the stress of the competition could trigger a negative mood profile and sleep disturbance which correspond to different responses of biomarkers related to the hypothalamo-pituitary-adrenal axis and the sympathetic nervous system activity, cortisol, sAA and CgA.